2016
DOI: 10.1103/physrevlett.117.163201
|View full text |Cite
|
Sign up to set email alerts
|

Universal Three-Body Physics in Ultracold KRb Mixtures

Abstract: Ultracold atomic gases have recently become a driving force in few-body physics due to the observation of the Efimov effect. While initially observed in equal mass systems, one expects even richer few-body physics in the heteronuclear case. In previous experiments with ultracold mixtures of potassium and rubidium, an unexpected nonuniversal behavior of Efimov resonances was observed. In contrast, we measure the scattering length dependent three-body recombination coefficient in ultracold heteronuclear mixtures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 55 publications
1
51
0
2
Order By: Relevance
“…Recent studies on the three-body recombination coefficient of the K-Rb systems [20,23,24] showed that there is no Efimov-related resonance in the region of 200 a 0 < |a| < 3000 a 0 . Furthermore, the single-channel universal theory on the heteronuclear Efimov resonance for broad resonance predicts that there is no resonance in the region of |a| < 2800 a 0 [14].…”
Section: K Atoms Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on the three-body recombination coefficient of the K-Rb systems [20,23,24] showed that there is no Efimov-related resonance in the region of 200 a 0 < |a| < 3000 a 0 . Furthermore, the single-channel universal theory on the heteronuclear Efimov resonance for broad resonance predicts that there is no resonance in the region of |a| < 2800 a 0 [14].…”
Section: K Atoms Andmentioning
confidence: 99%
“…Additionally, we enhanced the three-body loss by increasing the atomic density [41]. The observed three-body loss coefficient (Fig.2) did not show any Efimov-like structures [24].…”
Section: K Atoms Andmentioning
confidence: 99%
See 1 more Smart Citation
“…This motivated for example the first experimental measurement in heteronuclear atomic systems by the Florence group [7] and, more recently, the experiments reported in Refs. [8][9][10][11]. Such systems also exist in nuclear physics as neutron-rich halo nuclei, which are weakly bound nuclei consisting of a tightly bound core and a small number of valence neutrons [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, interest has turned to mixtures of quantum gases and the tuning of interspecies interactions. This interest is motivated by the study of exotic phases such as supersolids [19], the heteronuclear Efimov scenario for a three-body system [20][21][22], boson-mediated superfluids [23], quantum phases that involve composite fermions [24], mixtures under simultaneous superfluidity [25], and the possibility of forming samples of ultracold polar ground-state molecules [26]. In particular, the electric dipole moment of heteronuclear molecules gives rise to anisotropic, long-range dipole-dipole interactions that contrast with the isotropic, short-range interaction in atomic experiments [27,28].…”
Section: Introductionmentioning
confidence: 99%